3D Ordered Co@NC Skeleton for Bifunctional Oxygen Reduction and Oxygen Evolution Reaction Electrocatalysts. Issue 6 (3rd February 2021) - Cai, Zihe; Lin, Shengxuan; Xiao, Jiajia; Muhmood, Tahir; Hu, Xiaobin
Abstract: Transition metal@nitrogen–carbon (M@NC) catalysts are greatly desired for zinc–air batteries due to the promising oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) properties. Herein, a uniformly distributed Co@NC catalyst derived from metal–organic frameworks is developed. The CoN x species and Co nanoparticles encapsulated in carbon networks promote ORR and OER kinetics synergistically. Moreover, a novel structure is designed for exposing active sites, which consists of 3D macroporous skeleton embedded in carbon fiber paper. It is revealed that the outstanding ORR and OER properties attribute to the sufficient active area obtained from porous structure and ultra‐thickness (280 µm). Besides, interconnected macropores provide abundant channels for mass transport. The liquid ZABs assembled using 3DOMCo@NC‐1‐090 displays outstanding performances. Abstract : A novel free‐standing 3DOM carbon skeleton companied with abundant CoN x and Co nanoparticles encapsulate in carbon networks uniformly. The sufficient active area and interconnected channels promote the ORR and OER kinetics and mass transport. The zinc–air batteries based on 3DOM Co@NC shows promising performances.